Oracle Application Express 4 Recipes - Zehoo, Edmund; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
Oracle Application Express 4 Recipes provides an example-based approach to learning Application Express$1 (Bthe ground-breaking, rapid application development platform included with every Oracle Database license. The recipes format is ideal for the quick-study who just wants a good example or two to kick start their thinking and get pointed in the right direction. The recipes cover the gamut of Application Express development. Author and Application Express expert Edmund Zehoo shows how to create data entry screens, visualize data in the form of reports and charts, implement validation and back-end logic, and much more. Solutions are presented in an easy problem/solution format, which you can copy and adapt for your own use. Detailed discussion for each solution deepens your understanding and aids in customizing the solutions to fit your particular development challenges. Teaches Application Express via an example-based format Takes you from beginner to intermediate level Shows how to build a fully-functional web store in just one hours
Keywords: Computer science; Database management; Computer Science; Computer Science, general; Database Management